Self-esteem, defensive strategies and social intelligence in the Adolescence - MALTESE, Agata; ALESI, Marianna; Alù, AGM (Procedia - Social and Behavioral Sciences, 2012)
A variety of studies documented that self-esteem is related to protective strategies including self-handicapping and causal attributions in the school domain. In particular, these defensive modalities, both proactive and retroactive, refer to some of the maladaptive strategies employed by an individual, respectively before and after performing difficult and threatening tasks, to protect him or herself and maintain a positive self-esteem. Within the theoretical framework of self-regulation, the maintenance and the protection of competency self-images implies the social intelligence model of personality (Cantor and Kihlstrom, 1987). The social intelligence, which includes self-concept, autobiographical memories, decision rules, is a multidimensional construct that people use to solve their daily life problems. An example is to preserve the self-image in external threatening contexts by the use of defensive strategies (Rodhewalt and Vohs, 2005). The aim of this study is to explore the Proactive And Retroactive Excuses used by adolescents and their relationship with Self-Esteem and the Social Intelligence's domains. The subjects in this study were 786 attending the 3th or the 5th final years of high school (humanistic, scientific, technical and pedagogic schools) with the mean age of 17.2 years. Their self-esteem was measured by the Self-Esteem Scale (Rosenberg, 1965). Students were administered a questionnaire aimed at evaluating the Defensive Strategies consisting of 20 items, 10 for the proactive excuses and 10 for the retroactive ones (Alesi and Pepi, 2011). Finally they were given the Tromso Social Intelligence Scale (Silvera, Martinussen and Dahl, 2001) articulated in three subscales: Social Information Processing, Social Awareness and Social Skills. On the whole, results indicate negative significant correlations between Negative Self-Esteem, Proactive Excuses and all the three Social Intelligence domains. Retroactive Excuses correlate significantly and negatively only with Negative Self-Esteem. Instead, ...